'Round Robbins Jerome Robbins's Fancy Free and Jerome Robbins on DVD - McDonagh, Maitland; Goldner, Nancy (Dance Books Ltd., Alton,Hampshire (UK), 2002)
Fancy Free and Jerome Robbins on DVD. Midler inhabits the role with a fervor that verges on the obscene and sings the hell out of it. PALABRAS CLAVE: Fancy Free, Jerome Robbins, Broadway, Hollywood, musicals, West Side Story, Fiddler on the Roof, The King and I.
Jerome Robbins on DVD: The King and I (20th-Century Fox Home Enterteiment, widescreen). West Side Story (MGM Home Entertaiment, widescreen). Fiddler on the Roof Special Edition (MGM Home Entertaiment, widescreen, with supplements).